Google Us! Capital Area District Libraries Gets Noticed with Google Ads Grant - Knox, Sheryl; Smiley, Trenton (Information Technology and Libraries, 2020)
Capital Area District Libraries enrolled in Googe Ad Grants in 2018 and receives up to 10,000 of in-kind Google Ads each month. This article describes how we obtained the grant, the campaigns we've developed, and the impact it has made on visits to our online branch.